Homogeneous Gamma Knife boost following Linac-RT: a feasibility study for nasopharyngeal carcinoma - Spaniol, Manon; Abo-Madyan, Yasser; Ruder, Arne Mathias; Schweizer, Beate; Fleckenstein, Jens; Giordano, Frank Anton; Stieler, Florian (Physica medica, 2025)
Purpose - Radiotherapy plays a critical role in the treatment of nasopharyngeal carcinoma (NPC). However, the number and close proximity of organs at risk (OAR) hampers dose escalation using classical techniques. The Leksell Gamma Knife® (LGK, Elekta AB) achieves a steep dose gradient, which might be beneficial to apply sequential/upfront boosts to these tumors. This study explores the feasibility of fractionated, homogeneous LGK Icon boost compared to a linear accelerator (LINAC) boost. - Methods - Eight NPC patients treated with LINAC-based therapy at our institution were retrospectively analyzed. Each patient received a base plan (60/2Gy) to the primary tumor and nodes, followed by a boost (10/2Gy) targeting the primary tumor. LGK boost plans were generated using a research prototype version of LGK Lightning® (Elekta AB) for enhanced homogeneity in order to reduce hot spots within critical regions. Gradient index (GI), Paddick conformity index (PCI), and institutional OAR constraints were evaluated. - Results - Over all patients, the LGK boost plans had improved GI compared to the LINAC boost plans (3.11vs.5.46) and decreased PCI (0.79vs.0.81). The sum of base and LGK boost plans showed overall lower OAR doses [0.5-1.3 Gy] compared to the sum of base and LINAC boost. With the LGK boost plans, hot spots inside the PTV were in mean 1.6 Gy higher compared to the LINAC boost. - Conclusion - This study demonstrated the feasibility and dosimetric benefits of using fractionated LGK boost following LINAC base treatment for NPC. The prototype version effectively reduced doses to OAR and controlled hot spots within the target.